1991
DOI: 10.1101/gad.5.3.389
|View full text |Cite
|
Sign up to set email alerts
|

Does steric interference between splice sites block the splicing of a short c-src neuron-specific exon in non-neuronal cells?

Abstract: The neuron-specific splicing of the mouse c-src N1 exon was analyzed. Model src genes, transiently expressed in HeLa and LA-N-5 neuroblastoma cells, were assayed for the insertion of the 18-nucleotide neuron-specific N1 exon into their product mRNA. The normal clone fails to use this exon in HeLa cells but inserts the exon into 50% of the mature mRNA in LA-N-5 cells. When the exon and flanking intron sequences are placed between two adenovirus exons, the N1 exon is still only inserted in the neural cells. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
132
3

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(138 citation statements)
references
References 67 publications
3
132
3
Order By: Relevance
“…In general, small exons are thought to be poorly recognized by the splicing machinery, possibly as a result of steric hindrance between snRNPs and other splicing factors (22,43); presumably to compensate for this, small CS exons tend to be accompanied by stronger splice site signals and splicing enhancer motifs (22,44). Because AS exons tend to be small (21,23), it is important to consider the possibility that the increased sequence conservation in AS exons is due solely to their size.…”
Section: Discrimination Of Misclassified Exonsmentioning
confidence: 99%
“…In general, small exons are thought to be poorly recognized by the splicing machinery, possibly as a result of steric hindrance between snRNPs and other splicing factors (22,43); presumably to compensate for this, small CS exons tend to be accompanied by stronger splice site signals and splicing enhancer motifs (22,44). Because AS exons tend to be small (21,23), it is important to consider the possibility that the increased sequence conservation in AS exons is due solely to their size.…”
Section: Discrimination Of Misclassified Exonsmentioning
confidence: 99%
“…Another group of potential splicing regulators is the heterogeneous nuclear ribonucleoprotein (hnRNP) fam ily of proteins, which bind to unspliced hnRNA in mam malian cells, but again these proteins are not highly tis-sue specific (Dreyfuss et al 1993). As yet there are no cell type-specific splicing factors identified in mammalian cells, and there are few systems where a regulated splic ing event has been reconstructed in vitro (Ge and Manley 1990;Black 1992).…”
mentioning
confidence: 99%
“…We are using the mouse c-src gene as a model system for study ing neural-specific splicing in mammalian cells (Black 1991(Black ,1992. c-src is a proto-oncogene encoding a protein tyrosine kinase (Cooper 1990;Bolen 1993).…”
mentioning
confidence: 99%
“…Lower efficiencies for the splicing of small exons (Black 1991;Dominski and Kole 1991;Hwang and Cohen 1997) and large exons (Peterson et al 1994;Sterner et al 1996;Borensztajn et al 2006) have been observed previously. Surprisingly, when we used different splice site sequences, we found a striking difference in exon size dependence.…”
Section: Discussionmentioning
confidence: 72%